STUDENTS’ PERCEPTIONS ON THE USE OF INTERNET AS LEARNING MEDIA IN READING CLASSROOM - Nurhasanah Nurhasanah; Bambang Sulistyo; Merie Agustiani; Eviyatin Nisa Ulya (Universitas Putera Batam, 2020)
This study investigated students’ perception of using the internet as learning media in reading comprehension skills. This study uses descriptive statistics. The objective of the research was to find out the students’ perception of using the internet as learning media in the reading comprehension skill of the English Education Study Program at Baturaja University. The population of this research was 79 students of English Study Program. The researcher only took 54 students as the sample by applying purposive sampling. The data was collected through the questionnaire that consisted of 20 statements. Then the researcher used five points of Likert scale for analyzing the data. The result of this research there agreed (4.03) students had a positive perception of using the internet as learning media in reading comprehension skills. It means that the internet is a facility to improve his proficiency in language skills. So the use internet for English learning makes language learning an easier process by being fun, interactive, and interesting.